1995
DOI: 10.1093/oxfordjournals.aje.a117541
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Hospital Admissions for Cardiovascular Disease in Detroit, Michigan

Abstract: In the December 1952 smog disaster in London, a substantial increase in mortality was closely associated with the increase in air pollution. Deaths from cardiovascular causes were elevated as well as respiratory deaths. The increase was greatest in the elderly. Hospital admissions were increased for both respiratory and cardiovascular diseases. Since then, many studies have reported associations between lower concentrations of air pollution and daily mortality. Little attention has been paid to the question of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
193
1
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(212 citation statements)
references
References 54 publications
11
193
1
7
Order By: Relevance
“…Unfortunately, information on some known risk factors for fetal growth development, such as maternal race, education, cigarette smoking, caloric intake, alcohol consumption, paternal weight and height, and socioeconomic status was not available. However, these risk factors are likely to vary independently of changes in ambient pollutant levels, and therefore should not confound the associations between air pollution and fetal growth restrictions observed here (Rothman, 1993;Schwartz and Morris, 1995;Liu et al 2004). …”
Section: Discussionmentioning
confidence: 89%
“…Unfortunately, information on some known risk factors for fetal growth development, such as maternal race, education, cigarette smoking, caloric intake, alcohol consumption, paternal weight and height, and socioeconomic status was not available. However, these risk factors are likely to vary independently of changes in ambient pollutant levels, and therefore should not confound the associations between air pollution and fetal growth restrictions observed here (Rothman, 1993;Schwartz and Morris, 1995;Liu et al 2004). …”
Section: Discussionmentioning
confidence: 89%
“…Rates of incidence found through the present study fall within the previous orders of magnitude. In Michigan, USA (1986USA ( -1989, it was found that PM 10 induces an increase in hospital admissions due to ischemic heart disease and heart failure at a rate of 1.018% and 1.024%, respectively, while heart-failure admissions could as well reflect increasing CO levels at a rate of 1.022% (Schwartz and Morris 1995). Such an association-at a rate of 1.10-1.37% when CO increased by 10 mg kg −1 -could also be found through a study in seven US cities, 1986-1989.…”
Section: Resultsmentioning
confidence: 99%
“…CO has also been associated with admissions for cardiovascular events (16)(17)(18)(19). Martins and colleagues (20) showed a significant association between elderly patient hospital admissions due to cardiovascular diseases and SO 2 in São Paulo, Brazil.…”
Section: Discussionmentioning
confidence: 98%